Level-resolved distorted-wave cross-sections of electron impact ionization of Ar5+ - YUMAK YAHŞİ, AYŞE; YAVUZ, İLHAN; ALTUN, ZİKRİ (Institute of Physics Publishing, 2009)
Electron impact ionization cross sections of Ar5+ were calculated using configuration-average (CADW) and level-resolved (LRDW) distorted-wave methods. Direct ionization cross-sections of 2s, 2p, 3s and 3p subshells were calculated within a CADW approximation. The contributions from the excitation autoionization channels were evaluated assuming single excitations from the 2s, 2p, and 3s subshells and in both CADW and LRDW methods. The radiative stabilization of the excitation autoionization channels were found to reduce the excitation autoionization by a small amount. © 2009 IOP Publishing Ltd.